The burden, trends, and projections of low back pain attributable to high body mass index globally: an analysis of the global burden of disease study from 1990 to 2021 and projections to 2050 - Chuan Zhang; Shanglin Zi; Quanzheng Chen; Shuna Zhang (Frontiers in Medicine, 2024)
ObjectiveTo systematically evaluate the global burden and trends of low back pain(LBP) associated with high Body Mass Index (BMI) and project future trends up to 2050 using Bayesian Age-Period-Cohort (BAPC) model, providing scientific evidence for prioritizing global preventive actions.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021 study, this research analyzes the disease burden of low back pain linked to high BMI globally, with Disability-Adjusted Life Years (DALYs) as the primary metric. We examined trends by gender, age, and exposure rate using Estimated Annual Percentage Change (EAPC) and projected future trends with the BAPC model.ResultsIn 2021, high BMI-related low back pain accounted for 8,363,759 DALYs, with an age-standardized rate of 97.66 per 100,000 population and an EAPC of 1.14. The DALYs rate varied significantly by country, with the United States, Australia, and Eastern Europe experiencing the highest rates, all exceeding 225 per 100,000 population. The burden has increased globally, with notable rises in China, Southeast Asia, South Asia, and Africa, where EAPCs surpassed 2.5. Regions with medium and high Socio-Demographic Index (SDI) showed the most substantial increases, with the DALY rate in high SDI areas rising from 118.84 to 161.80 per 100,000, and in medium SDI areas from 41.92 to 79.10 per 100,000. Throughout the period from 1990 to 2021, females consistently experienced a higher burden of high BMI-related low back pain than males, with their DALY rate increasing from 92.01 to 126.29 per 100,000. The impact of high BMI on low back pain intensified with age, peaking in the 70–74 age group at 294.13 per 100,000, and then declining to 196.43 per 100,000 in those aged 95 and above. The BAPC model projects that by 2050, the number of DALYs will reach 15,558,278, an increase of 7,806,121 from 2021.ConclusionFrom 1990 to 2021, the global burden of low back pain attributable to high BMI has intensified, particularly affecting females, younger elderly, and developed regions. With increasing global aging and obesity rates, the burden is expected to continue rising rapidly without sustained and effective targeted interventions.